Hyperbilirubinemia, C-reactive protein, total leucocyte counts and serum amylase as markers of gangrenous/perforated appendicitis - Dhaigude, Piyush; Joshi, Mayank; Zubair , S. M.; Akther, M. D. Jawed (International Surgery Journal, 2023)
Background: C-reactive protein, serum amylase, total leucocyte count, and total serum bilirubin have been used as adjuncts for the diagnosis of appendicitis. This study assessed the diagnostic value of these markers in patients with suspected acute appendicitis. Methods: CRP, serum amylase, total leucocyte count, and total serum bilirubin values among the patients who presented with acute appendicitis were compared among patients who had perforated appendix and non-perforated appendix. The diagnostic value of CRP and TSB markers as a predictor for perforation were compared in terms of sensitivity, specificity, PPVs, and NPV, and the diagnostic accuracy was assessed by AUC using receiver operating characteristic (ROC) curve analysis. Results: The values of TSB (mean 3.52, S.D 0.54, p<0.001), CRP (mean 9.84, S.D 1.30, p<0.001), amylase (mean 68.2, S.D 26.4, p<0.001) were found to be significantly correlated with complicated appendicitis. Conclusions: This study concludes that estimation of pre-operative values of TSB, CRP, and serum amylase as a part of routinely done blood investigations in patients with suspected appendicitis, helps the surgeon in diagnosing complicated types of appendicitis at an earlier stage, though it cannot be generalized due to the small sample size, further studies are needed to establish the conclusion of the study.